Water stress induced by mannitol in cotton cultivars - Echer, Fábio (2010)
The main goal of this work was to evaluate the effects induced by mannitol- water stress in the initial growing of cotton plants. The experiment was conducted as a completely randomized design, in factorial design 4 x 5, with 3 replications. Treatments were generated by the combination of four cotton cultivars (LD CV Frego; LD CV 02; FMT 701 and IAC 25) and five levels of water stress (0; -0.3; -0.6, -0.9 and -1.2MPa), obtained with mannitol solutions. Water potentials of -0.9 MPa reduced significantly the rate of cotton plants growth. The decrease of the water potential reduced the production of dry mass of the aerial part of all cultivars and increased the production of root dry mass on -0.6MPa potential. LD CV 02 cultivar exhibited a superior performance under water stress.